PERKEMBANGAN MASA ANAK/ SEKOLAH (FISIK, INTELEKTUAL, EMOSI, SOSIAL, MORAL, SERTA AGAMA) DAN IMPLIKASINYA PADA PENDIDIKAN AGAMA ISLAM - Yudistira Nugraha, Muhammad; Efendi, Ridwan; Yolanda; Harto, Kasinyo; Putra Pratama, Irja (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Early school childhood (6-12 years) is a crucial period for children's physical, psychological and cognitive development. Children experience an increase in physical strength, social maturity, and independence, and begin to develop a sense of responsibility and critical thinking skills. Elementary school childhood (6-12 years) is a period of very significant development in various aspects of physical, motor, cognitive, social, emotional, language, and moral. The method used in this research is literature, the data source is from books, articles, websites, then analyzed to draw conclusions. The results show that at this age, children show improvements in gross motor skills, more complex language abilities, as well as more mature cognitive development, including logical thinking. They also begin to develop social skills and a deeper understanding of emotions and social norms. In addition, the results obtained from this study are that support from the environment, such as parents, teachers and peers, is very important in encouraging children's development. Islamic religious education plays a crucial role in supporting this development, by teaching healthy living habits, strengthening intellectual abilities, and shaping children's social and moral character.